Trauma, resiliency, and risk perception of elderly survivors of the 2013 Bohol earthquake. - Cuizon, Faith Angel E.
This is a descriptive study which investigated the nature of trauma, resiliency, and risk perception of the elderly survivors of the 2013 earthquake in Sagbayan, Bohol. Twenty one (21) elderly survivors aged 60 years and above participated in the study through purposive sampling. Through an in-depth interview, results showed that there were no serious psychological effects brought about by the earthquake; however, they did experience some of the usual psychological responses such as fear and flashbacks. They had high levels of resiliency brought about by strong social support from their family, relatives, and friends. Before the earthquake, their risk perception revealed scores ranging from very low to medium levels of risk perception. After the earthquake, scores revealed that there was increase in their risk perception.